Efficiency of RSI Investment Strategy : A Comparative Study of Saudi Arabia, India, and China - Nidhi,; Malik, Narinder Singh; Singla, Rajat (Indian Journal of Finance, 2023)
Purpose : The present study is focused on testing the performance of the relative strength index (RSI) minutely on daily prices of stock indices of three sample countries. As the interest in investing in the stock market is growing day by day, the need to test the performance of technical indicators is also enhanced. Methodology : The closing prices of three indices from the sample markets were investigated for 14 years, from January 2008 to December 2021, by applying the 30/70 rule of the RSI. The whole period of sample data from 2008 to 2021 has been divided into two smaller sub-periods of 7 years each in order to test the performance of the oscillator during the short period. Sub-period I is from January 2008 to December 2014; Sub-period II is from January 2015 to December 2021. While comparing the buy and hold strategy with RSI, one form has assumed that once the buy or sell decision is made, the same will be held for 10 days. Findings : A 1% significance level was used to find the majority of the results to be statistically significant. Twenty-seven places, or 50% at the 1% level, and three results, or 5.55% at the 5% and 10% levels, were determined to be statistically significant out of the 54 total results. At various levels, 61.12% of the long, short, and long-short positions are determined to be statistically significant. Practical Implications : RSI is the most frequently used oscillator by investors for making investment decisions; thus, it becomes essential to minutely study the profitability of the oscillator academically. Our study is not free from limitations and allows scope for future researchers to study the performance of oscillators along with other techniques of technical trading rule, and it can be tested on different samples of markets. Originality : The previous research focused either on testing moving averages or testing plain crossover rules of RSI. The current work tested different forms of the oscillator, applying a holding period of days.